The Homotopy Perturbation Method for Solving Some Types of Nonlocal Problems with Some Real Life Applications - Khaleel, Ahlam J (Al-Nahrain Journal of Science, 2012)
In this paper, we use the homotopy perturbation method for finding the solutions of the nonlocal problems that consist of the one-dimensional heat equation together with nonlocal conditions and the nonlocal problems that consist of the parabolic linear integro-differential equations together with nonlocal conditions. Also, some numerical examples are presented to explain the efficiency of this method. Moreover, some real life applications for the nonlocal problems are solved via this method.